2014
DOI: 10.5152/kd.2013.07
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalance of Measles, Rubella, Mumps, Varicella, Diphtheria, Tetanus and Hepatitis B in Healthcare Workers

Abstract: ÖzetAmaç: Celal Bayar Üniversitesi Hafsa Sultan Hastanesi personelinde aşıyla önlenebilir hastalıklardan kızamık, kızamıkçık, kabakulak, difteri, tetanos, suçiçeği ve hepatit B antikor (IgG) dü-zeylerinin belirlenmesi ve bağışık olmayan kişilerin aşılanmaları konusunda teşvik edilmeleri amaçlanmıştır. Yöntemler: Antikor düzeyleri "enzyme-linked immunosorbent assay" (ELISA) yöntemiyle belirlenmiştir. Katılımcıların demografik özellikleri, hastalık geçirme öyküsü, aşılanma ve kesici-delici aletle yaralanma durum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 11 publications
0
8
1
2
Order By: Relevance
“…In the study of Cılız et al 308 (99.7%) of the health-care workers were found to be positive for antibodies against measles, mumps and varicella and 299 (96.8%) of the health-care workers were found to be positive for antibodies against rubella [5]. In the study of seropositivity were found to have 92.2%, 98.2%, 94% and 94.3% respectively in health-care workers [6].…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…In the study of Cılız et al 308 (99.7%) of the health-care workers were found to be positive for antibodies against measles, mumps and varicella and 299 (96.8%) of the health-care workers were found to be positive for antibodies against rubella [5]. In the study of seropositivity were found to have 92.2%, 98.2%, 94% and 94.3% respectively in health-care workers [6].…”
Section: Discussionmentioning
confidence: 94%
“…In the study done by Cılız et al, according to the disease history of the participants at the higher rates they remembered diseases that varicella zoster (56.6%), mumps (47.9%) and measles (34.3%) [5]. Also, in the study of Sengoz et al, according to the disease history of the participants, they mostly remembered mumps (61.7%), measles (59.6%) and varicella zoster (59.1%) [6].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Manisa'da yapılan bir araştırmada kızamık geçirme öyküsü bu araştırmanın sonuçlarına benzemektedir. Ancak, suçiçeği ve kabakulak daha fazla anımsanmaktadır (13). Hastalığı geçirmeyen veya geçirip geçirmediğini bilmeyen sağlık personelinin serolojik test sonuçlarına göre aşılanmaları gerekmektedir.…”
Section: Yöntemlerunclassified
“…Ancak, en fazla aşı yaptırma düzeyi hekimlerin de içinde olduğu profesyonel grupta ve hemşirelerin içinde bulunduğu teknik grupta %73 ile %84 arasında değişmektedir. Manisa'da yapılan çalışmada da hekimlerde aşılama en yüksek bulunmuştur (13).…”
Section: Yöntemlerunclassified